Mutation‐specific antibody detects mutant BRAFV600E protein expression in human colon carcinomas. Issue 15 (8th May 2013) - Sinicrope, Frank A.; Smyrk, Thomas C.; Tougeron, David; Thibodeau, Stephen N.; Singh, Shalini; Muranyi, Andrea; Shanmugam, Kandavel; Grogan, Thomas M.; Alberts, Steven R.; Shi, Qian
Abstract : BACKGROUND: A point mutation (V600E) in the BRAF oncogene is a prognostic biomarker and may predict for nonresponse to anti‐EGFR antibody therapy in patients with colorectal carcinoma. BRAF V600E mutations are frequently detected in tumors with microsatellite instability and indicate a sporadic origin. We used a mutation‐specific antibody to examine mutant BRAF V600E protein expression and its concordance with BRAF V600E mutation data. METHODS: Primary stage III colon carcinomas were analyzed for BRAF V600E mutations in exon 15, and 50 BRAF V600E mutation carriers and 25 wild‐type tumors were selected for analysis of BRAF proteins by immunohistochemistry (IHC). IHC was performed in archival tissue specimens using a pan‐BRAF antibody and a mutation‐specific antibody against BRAF V600E proteins. Staining was scored by 2 pathologists who were blinded to clinical and mutation data. RESULTS: Using a pan‐BRAF antibody, total BRAF protein expression was observed in the tumor cell cytoplasm in 74 of 75 colon carcinomas. A mutation‐specific antibody identified diffuse cytoplasmic staining of mutant BRAF V600E proteins in 49 of 74 cancers. Analysis using a polymerase chain reaction‐based assay revealed that all 49 of these cancers carried BRAF V600E mutations. In contrast, BRAF V600E staining was absent in all 25 tumors that carried wild‐type copies of BRAF . CONCLUSIONS: A BRAF mutation‐specific (V600E) antibody detected tumors with BRAF V600E mutations and exhibited complete concordance with a DNA‐based method. These results support the use of IHC as a simplified strategy to screen colorectal cancers for BRAF V600E mutations in clinical practice. Cancer 2013 ;119:2765–2770. © 2013 American Cancer Society . Abstract : Immunohistochemical analysis of mutant (substitution of valine by glutamic acid at position 600 [V600E]) v‐Raf murine sarcoma viral oncogene homolog B1 (BRAF) protein expression yields highly concordant results with a DNA‐based assay for the detection of BRAF V600E mutations in human colon carcinomas. This finding suggests that immunohistochemistry is an alternative approach for detecting BRAF V600E mutations in clinical practice.